THE IMPACT OF ISLAMIC JURISPRUDENCE ON LEGAL DRAFTING - Dr. Shurooq Kamel Ismail (Scholars Digest Publishing, 2025)
Praise be to Allah, Lord of the Worlds, and peace and blessings be upon the one sent as a mercy, guidance, light, and shining lamp. And upon his family and his pure and righteous companions, and those who followed them in goodness until the Day of Judgment...Now then.
Keywords: Impact, principles of Islamic jurisprudence, Legal draftin.